TIKTOK AND INSTAGRAM AS CONTEMPORARY MEDIA FOR ISLAMIC DA'WAH - Iriswan Iriswan; Azman Ab Rahman; Moh Ali (Karimiyah: Journal of Islamic Literature and Muslim Society, 2026)
The rapid proliferation of social media platforms, particularly TikTok and Instagram, has fundamentally redefined the landscape of Islamic da'wah in the contemporary digital era. This study examines how Muslim preachers (da'i) strategically harness the affordances of these two platforms to disseminate Islamic teachings, cultivate religious communities, and adapt traditional preaching methods to algorithmically governed digital environments. Employing a systematic literature review methodology, this article synthesises findings from a corpus of recent empirical studies published between 2019 and 2025, with particular attention to works examining the Indonesian, Malaysian, Kazakhstani, Nigerian, and Bangladeshi contexts. The analysis reveals that TikTok's short-form video format and recommendation algorithm have created unprecedented opportunities for viral religious content, while Instagram's visual storytelling tools including Stories, Reels, and IGTV support a more sustained engagement with Islamic values and aesthetics. Both platforms, however, simultaneously introduce profound challenges: the commodification of religious authority, the risk of doctrinal distortion under the pressure of algorithmic optimisation, ethical tensions surrounding entertainment-oriented content, and the contested fragmentation of traditional scholarly legitimacy. This article further identifies key thematic trends including the emergence of digital da'i influencers, the construction of participatory Islamic communities online, the role of platforms in shaping moderate Islamic discourse for Generation Z, and the gendered dimensions of digital preaching. The study concludes that effective and ethically grounded digital da'wah requires a deliberate integration of Islamic communicative ethics with platform-specific content strategies, and that future research must more rigorously interrogate the algorithmic mediation of religious knowledge in Muslim-majority societies.